1993
DOI: 10.1161/01.hyp.21.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Regional angiotensin II production in essential hypertension and renal artery stenosis.

Abstract: To study regional metabolism and production of angiotensin II, we measured steady-state plasma levels of 12S I-angiotensin I and II and endogenous angiotensin I and II in the aorta and the antecubital, femoral, renal, and hepatic veins during systemic infusion of 125 I-angiotensin I or II. Extraction of arterially delivered angiotensin II ranged from 30-50% in the limbs to 80-100% in the renal and hepatomesenteric vascular beds both in essential hypertension (n=13) and in unilateral renal artery stenosis (n=7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 36 publications
4
44
1
1
Order By: Relevance
“…The slightly increased plasma angiotensin II level in the hyper-ACE individuals can be explained by increased conversion during blood sampling as a consequence of the increased amount of ACE. 34 In contrast to our hyper-ACE individuals, in subjects with the DD genotype, both membrane-bound and soluble ACE are elevated. 35 This might explain that some authors have found that the DD genotype influences cardiovascular morbidity, whereas we do not find clinical effects in the hyper-ACE individuals.…”
Section: Discussioncontrasting
confidence: 76%
“…The slightly increased plasma angiotensin II level in the hyper-ACE individuals can be explained by increased conversion during blood sampling as a consequence of the increased amount of ACE. 34 In contrast to our hyper-ACE individuals, in subjects with the DD genotype, both membrane-bound and soluble ACE are elevated. 35 This might explain that some authors have found that the DD genotype influences cardiovascular morbidity, whereas we do not find clinical effects in the hyper-ACE individuals.…”
Section: Discussioncontrasting
confidence: 76%
“…Ang-(1-7), at concentrations Յ1 mol/L, did not affect the generation of Ang II or the half life of Ang I. Higher concentrations of Ang-(1-7) interfered with the Ang II (but not the Ang I) assay, 14 thus not allowing us to demonstrate that these concentrations also suppressed generation of Ang II. However, the latter is highly likely in view of the similar increase in Ang I half life in the presence of the highest Ang-(1-7) concentration as in the presence of the highest quinaprilat and captopril concentrations.…”
Section: Ang I Metabolism In Human Blood Plasmamentioning
confidence: 73%
“…Previous studies in pigs 14 and humans 20 demonstrated that the 125 I-Ang I-to-II conversion rate, both in vitro and in vivo, is about two times the Ang I-to-II conversion rate and that the rates at which 125 I-Ang I and Ang I are degraded into peptides other than 125 I-Ang II and Ang II are not different. The 125 I-Ang II and Ang II degradation rates are also not different.…”
Section: Discussionmentioning
confidence: 96%
“…The 125 I-Ang II and Ang II degradation rates are also not different. 20 The fact that the 125 I-Ang I-to-II conversion rate is somewhat higher than the Ang I-to-II conversion rate may have led us to overestimate the amount of Ang II in cardiac tissue that is derived from Ang I in the circulation. Therefore, this does not invalidate our conclusion that most of the Ang II in cardiac tissue is generated from in situ-synthesized rather than blood-derived Ang I.…”
Section: Discussionmentioning
confidence: 99%